The use of modern technologies in digital violence against pupils and students - Jevtic, Radoje B. (Education and Research in Health Sciences, 2023)
Abstract: Today`s world and its functioning cannot be imagined without products of modern technologies. Benefits of their use are enormous Modern life presents life with lot of fast and big technological changes. These changes, beside the rest, included the use of many new technical devices that use electrical energy and produce electromagnetic radiation (mobile phones, laptops, tablets, TV devices, antennas, light devices etc.). Of course, mobile phone, laptop and tablet presents one of the most frequently used devices in the last time. Their use has a lot of benefits, related to work and life. But, beside benefits, there are some so called bad effects. The first association on bad effects related to modern electrical devices, so as mobile phone, is electromagnetic radiation. Beside noted bad effects, these devices can be used in the service of digital violence and other bad forms of behaviour or criminal. This paper was written to show the use of mobile phone, laptop, desktop and tablet in the work and life of pupils and students, potential exposure of pupils and students to digital violence and presence and influence of digital violence at pupils and students. The researches presented in this paper was realised by the author of this paper and included pupils from elementary and secondary schools in Niš so as students from faculties of Niš University.